E-commerce adoption and small business in the global marketplace : tools for optimization - Thomas, Brychan, 1955-; Simmons, Geoff, 1971- (Hershey, PA : Business Science Reference, 2010)
'This book focuses on isolating what determines the adoption of e-commerce applications that will optimize potential opportunities presented to small businesses through adoption'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Electronic commerce; Small business